Blood and marrow transplant for lymphoma patients with HIV/AIDS - Wagner-Johnston, Nina D. (2008)
PURPOSE OF REVIEW: Important strides in the management of patients with HIV/AIDS-related lymphomas have been made in recent years. This review will discuss the role of bone marrow or peripheral stem-cell transplantation as a modality for patients with HIV and lymphoma. RECENT FINDINGS: In the era of highly active antiretroviral therapy, patients with HIV-associated lymphoma are generally being treated with standard or only slightly modified chemotherapy regimens. Autologous bone marrow and stem-cell transplant approaches in lymphoma patients have been successful. Case reports suggest that allogeneic transplantation for patients with HIV and hematologic malignancies merits further investigation. SUMMARY: High-dose hematopoietic stem-cell therapies with curative intent should be considered as standard therapeutic options in patients who otherwise are appropriate for such therapies.